Influence of wind speed on rain-based attenuation at Ku-band for earth-satellite links in Nigeria - Joseph Sunday Ojo; Isaac Olawale Sunday; Elijah Olusayo Olurotimi (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The peculiarity of the tropical climate shows that when the quality of service (QoS) on Satellite-Earth propagation links is to be determined, the statistics of rain-based attenuation (RbA), storm speed, and their impacts are the important parameters to be considered, especially at frequencies above 10 GHz. This paper assesses the influence of storm speed in estimating RbA at Ku-band, based on 2-year rain rate data obtained using automatic weather station (AWS) and RbA beacon measurements in Nigeria. The rain rates based on the time series were employed to deduce the time series RbA based on the synthetic storm technique (SST) algorithm. The results show a seasonal pattern of rain rate that correlates with the SST-based RbA. The RbA generated closely follows suit with the beacon measurement, especially under low wind speed, and outperforms the international telecommunications union–radiocommunication sector (ITU-R) model based on the lowest metric measures. However, at a higher storm speed, the RbA generated deviated widely from the measured RbA values by about 16%. These results are crucial for figuring out what needs to be done to protect QoS in a tropical area where wind and rain are common.